Laboratory validation of an LC-MS/MS method for the detection of ractopamine, clenbuterol and salbutamol in bovine and swine muscle at sub-μg kg–1 regulatory limits - Montes Nino, Alfredo M. (2017)
Ractopamine (RAC), is a β-adrenergic agonist increasingly used in the swine and cattle industry. This compound redirects nutrients to favour leanness rather than fat deposition, improves growth and carcass traits gaining higher economic benefit to producers. Countries around the world are split over whether to allow the use of RAC in meat production. Clenbuterol (CLB) and salbutamol (SLB) are anillinic and phenolic β-agonists, respectively, with the same capacity of producing economic benefits for the meat sector. However, they are prohibited because of the potentially adverse reactions they can cause in consumers. The three β-agonist compounds have been included in the Brazilian National Regulatory Survey and consequentially there is an eminent need for reliable methods capable of detecting those substances at the same time and reduce analytical costs. Therefore, an LC-MS/MS method for the simultaneous determination of residual RAC, CLB and SAL in swine and cattle muscle was developed and validated with quantification levels respecting the action levels established for Brazil which are 0.1, 0.2 and 5 µg kg–1 for RAC, CLB and SAL, respectively. Samples were quantified using RAC-d5, CLB-d9 and SLB-d6 as internal standards. The validation was performed according to European Union Decision 2002/657, which includes criteria (CCα, CCβ, recovery, repeatability, reproducibility and calibration curve). The method meets the Brazilian regulatory requirement that establishes criteria and procedures for the determination of parameters such as CCα, CCβ, precision and recovery. CCα values were 0.02, 0.21 and 5.42 µg kg–1 for RAC, CLB and SAL, respectively, in bovine and swine muscle samples; CCβ values were 0.03, 0.22 and 5.8 µg kg–1 for RAC, CLB and SAL, respectively, in bovine and swine muscle samples. Average recoveries fortified with 0.05–7.5 µg kg–1 of the studied β-agonist leads around 95%. The method was demonstrated to be suitable for the determination of RAC, CLB and SLB in swine and cattle muscle samples.